Tyrosine kinase inhibitors in the first-line treatment for metastatic nonclear cell renal carcinoma: A retrospective analysis of a national database - Poprach, Alexandr; Rumanova, Kristina; Lakomý, Radek; Chloupková, Renata; Stanik, Michal; Pokrivcak, Tomas; Kiss, Igor; Slaby, Ondrej; Studentova, Hana; Melichar, Bohuslav; Juracek, Jaroslav; Fiala, Ondrej; et al. (Urologic oncology, 2019)
BACKGROUND: Nonclear cell renal cell carcinoma (nccRCC) is a heterogeneous group of primary kidney tumors. The aim of the present retrospective study was to analyze outcomes of patients with nccRCC treated with tyrosine-kinase inhibitors (TKIs) based on a national registry. METHODS: The registry contained evaluable data of 93 nccRCC patients treated with first-line TKIs, including 87 patients with papillary renal cell carcinoma (RCC) and 6 patients with chromophobe RCC. The control cohort consisted of 1,788 patients with clear-cell RCC treated with first-line TKIs. Multivariable Cox proportional hazard model was used to evaluate the effect of potential prognostic factors on the survival measures. RESULTS: Median progression-free survival was 11.8 and 6.5 months in the clear cell renal cell carcinoma and nccRCC patients, respectively (P = 0.018), and median overall survival was 33.2 and 22.0 months, respectively (P = 0.007). In the multivariate analysis, independent factors associated with inferior progression-free survival included high tumor grade, worse Memorial Sloan Kettering Cancer Center risk group, absence of nephrectomy, and sunitinib (as opposed to pazopanib) as first-line targeted therapy. Independent predictors of inferior overall survival included nonclear cell histology, tumor grade, worse Memorial Sloan Kettering Cancer Center risk group, absence of nephrectomy, older age, and sunitinib as first-line targeted therapy. CONCLUSIONS: The present retrospective, registry-based study confirms that patients with nccRCC treated with TKIs have worse clinical outcomes compared to clear cell renal cell carcinoma patients with similar baseline characteristics.
Keywords: senioři; metastázy nádorů; Carcinoma, Renal Cell; senioři nad 80 let; Protein Kinase Inhibitors; Retrospective Studies; doba přežití bez progrese choroby; Middle Aged; mužské pohlaví; karcinom z renálních buněk; Adult; Aged, 80 and over; Neoplasm Metastasis; ženské pohlaví; retrospektivní studie; Humans; Progression-Free Survival; lidé středního věku; inhibitory proteinkinas; dospělí; Female; Aged; lidé; Male